Analysis of the role of innovation and efficiency in coastal destinations affected by tourism seasonality - Puertas Medina, Rosa María (2022)
This research analyses the relationship between efficiency, innovation and seasonality of the Spanish coasts for a five-year period (2015-2019). First of all, the nexus between the level of efficiency and changes in pro-ductivity, driven by improvements in innovation and/or efficiency, is determined using Data Envelopment Analysis and the Malmquist Index. Second, this paper proposes a synthetic index to measure seasonality and assess its connection with efficiency and innovation, using a cross efficiency approach to do so. Results show how the intensity of seasonality influences efficiency. In addition, it is observed that innovation can offset possible decreases in efficiency; as such, policies that promote both aspects are needed in the more seasonal destinations.(c) 2022 The Authors. Published by Elsevier Espana, S.L.U. on behalf of Journal of Innovation & Knowledge. This is an open access article under the CC BY license http://creativecommons.org/licenses/by/4.0/)